Diverse Requirements for Src-Family Tyrosine Kinases Distinguish Chlamydial Species - Mital, Jeffrey (American Society of Microbiology, 2011)
Chlamydiae are well known for their species specificity and tissue tropism, and yet the individual species and strains show remarkable genomic synteny and share an intracellular developmental cycle unique in the microbial world. Only a relatively few chlamydial genes have been linked to specific disease or tissue tropism. Here we show that chlamydial species associated with human infections, Chlamydia trachomatis and C. pneumoniae, exhibit unique requirements for Src-family kinases throughout their developmental cycle. Utilization of Src-family kinases by C. trachomatis includes tyrosine phosphorylation of the secreted effector Tarp during the entry process, a functional role in microtubule-dependent trafficking to the microtubule organizing center, and a requirement for Src-family kinases for successful initiation of development. Nonhuman chlamydial species C. caviae and C. muridarum show none of these requirements and, instead, appear to be growth restricted by the activities of Src-family kinases. Depletion of Src-family kinases triggers a more rapid development of C. caviae with up to an 800% increase in infectious progeny production. Collectively, the results suggest that human chlamydial species have evolved requirements for tyrosine phosphorylation by Src-family kinases that are not seen in other chlamydial species. The requirement for Src-family kinases thus represents a fundamental distinction between chlamydial species that would not be readily apparent in genomic comparisons and may provide insights into chlamydial disease association and species specificity.